Effect of sitagliptin therapy on triglyceride‐rich lipoprotein kinetics in patients with type 2 diabetes. Issue 12 (19th August 2014) - Tremblay, A. J.; Lamarche, B.; Kelly, I.; Charest, A.; Lépine, M.‐C.; Droit, A.; Couture, P.
<x xml:space="preserve">Abstract</x> Aim To investigate the effects of sitagliptin therapy on the kinetics of triglyceride‐rich lipoprotein (TRL) apolipoprotein (apo)B‐48, VLDL apoB‐100, apoE and apoC‐III in patients with type 2 diabetes. Methods Twenty‐two subjects with type 2 diabetes were recruited in this double‐blind crossover study, during which the subjects received sitagliptin (100 mg/day) or placebo for a 6‐week period each. At the end of each phase of treatment, the in vivo kinetics of the different apolipoproteins were assessed using a primed‐constant infusion of l‐[5, 5, 5‐D3]leucine for 12 h, with the participants in a constantly fed state. Results Sitagliptin therapy significantly reduced fasting plasma triglyceride (−15.4%, p = 0.03), apoB‐48 (−16.3%, p = 0.03) and free fatty acid concentrations (−9.5%, p = 0.04), as well as plasma HbA1c (placebo: 7.0% ± 0.8 vs. sitagliptin: 6.6% ± 0.7, p < 0.0001) and plasma glucose levels (−13.5%, p = 0.001), without any significant effect on insulin levels. Kinetic results showed that treatment with sitagliptin significantly reduced the pool size of TRL apoB‐48 by −20.8% (p = 0.03), paralleled by a reduction in the production rate of these particles (−16.0%, p = 0.03). The VLDL apoB‐100 pool size was also significantly decreased by sitagliptin therapy (−9.3%, p = 0.03), mainly because of a reduction in the hepatic secretion of these lipoproteins, although this difference did not reach statistical significance (−9.2%, p = 0.06). Conclusions Treatment with sitagliptin for 6 weeks reduced triglyceride‐rich apoB‐containing lipoprotein levels by reducing the synthesis of these particles.